Outcome of the gynecologic oncology patients surveillance network program - Prapaporn Suprasert (2018)
The gynecologic oncology patients surveillance network program was conducted with the collaboration of 5 provincial hospitals located in the north of Thailand (Chiang Rai, Lamphun Nan, Phayao and Phrae). The aim was to identify ways of reducing the burden and the cost to the gynecologic cancer patients who needed to travel to the tertiary care hospital for follow up. The clinical data of each patient was transferred to the provincial hospital by the internet via the website www.gogcmu.or.th. All the general gynecologists who participated in this project attended the training course set up for the program. From January 2011 to February 2014, 854 patients who were willing to have their next follow-up at the network hospitals close to their home were enrolled this project. Almost of them were residents in Chiang Rai province and the most common disease was cervical cancer. After the project had been running for 1 year, 604 of the enrolled patients and 21 health-care personnel who had participated in this project were interviewed to assess its success. Some 85.3% of the patients and 100% of the health-care personnel were satisfied with this project. However, 60 patients had withdrawn, the most common reason being the lack of confidence in the follow up at the local provincial hospital. In conclusion, it is possible to initiate a gynecologic oncology patients' surveillance network program and the initiation could reduce the problems associated with and the cost the patients incurred as they journeyed to the tertiary care hospital.